Unlocking tiny titans: 360 view of the quantum dots nanotechnology for dental applications - Alluhaidan, Tasneem; Garcia, Isadora Martini; Alexis, Meghan; Qaw, Masoumah; Collares, Fabrício Mezzomo; Williams, Mary Ann; Melo, Mary Anne S. (Frontiers in Dental Medicine, 2025)
Quantum dots (QDs) nanotechnology has gained significant attention in dentistry due to its unique properties, such as fluorescence, antimicrobial activity, and drug delivery potential. This review aims to identify the dental applications most actively incorporating QD technology and to examine the distinctive properties of QDs within Dentistry. Employing the Arksey and O'Malley five-stage framework, a systematic search was conducted across PubMed, EMBASE, and Scopus databases for English-language publications on QDs in dentistry. Scientific contributions were evaluated by analyzing publication volume, research trends, patents, and key areas of investigation. Of the 1,034 studies initially identified, 71 were fully screened, with 22 meeting the criteria for data extraction. Results showed that antimicrobial properties and bone regeneration are the primary focus areas for QDs in dental materials. Stock solutions and resin composites are the most common materials developed, with the studies primarily targeting ofenhancing antimicrobial capabilities and osteogenesis enhancement. Over the last decade, QDs have demonstrated potential in enhancing drug delivery, antimicrobial efficacy, and optical performance in dental materials. Despite their growing prominence, the clinical translation of QD-based technologies remains limited due to a lack of long-term studies.